From social majority to political minority: The stagnation of Islamic Parties in Indonesia - Ahmad Nurhuda; Suryadi Fajri; Taufiq Hidayat (Harmoni Sosial: Jurnal Pendidikan IPS, 2025)
This study explores the dynamics of Islamic political parties in Indonesia during the Reformasi era, which was marked by significant political system changes and evolving electoral landscapes. Despite Indonesia's status as the country with the world’s largest Muslim population, this research focuses on understanding the factors behind the lack of voter interest in Islamic political parties, especially after the 1998 reform. By utilizing a literature review method, this research aims to identify why these parties have struggled to gain significant votes in post-reform elections and what steps they could take to improve their relevance and image among voters. The findings indicate that although Indonesia holds the largest Muslim population globally, Islamic-based parties have faced consistent challenges in securing electoral success. After the reform, while many new Islamic parties emerged, none regained the dominance once held by the United Development Party (PPP) during the New Order era, when the PPP was the sole political platform for Muslims following party simplification by Soeharto’s regime. The study also reveals that the lack of voter interest can be attributed to Islamic parties’ failure to present concrete, appealing programs and voter dissatisfaction with their performance. Ultimately, this research aims to provide insights into how Islamic political parties can enhance their role in Indonesia’s democratic system by improving voter engagement and political participation.